Effects of two types of dynamic office workstations (DOWs) used at two intensities on cognitive performance and office work in tasks with various complexity. Issue 6 (3rd June 2021) - Schellewald, Vera; Kleinert, Jens; Ellegast, Rolf
Abstract: This study examines the possible effects on objective work performance while using two types of dynamic office workstations (DOWs). 20 participants each used one type with three intensities (seated, light, moderate) and completed a task battery assessing cognitive performance and office work with two levels of complexity. Repeated measures MANOVA showed a significant interaction effect for work performance between the type of workstation and intensity for the simple level and a significant main effect for intensity for the complex level. Comparing the types of DOWs to each other, accuracy of text processing differed when working sedentary. Using both devices with light and moderate intensity had a significant detrimental effect on mouse tasks compared to working sedentary, but none comparing the intensities. No further results indicated neither a detrimental nor an enhancing effect of using DOWs on cognitive performance and office-work related tasks, regardless of the intensity of use or the task complexity. Practitioner Summary: By using DOWs, light physical activity can be integrated while working at a desk. Results showed that using different types of DOWs with different intensities does have a detrimental effect on tasks requiring a high motor control, but not on cognitive or further office work-related tasks of various complexity. Abbreviations: DOW: dynamic office workstation; aLT: activeLife Trainer; DB: deskbike; RPE: rated perceived exertion; MANOVA: multivariate analysis of variance; ANOVA: analysis of variance